The Idea and Models of Civil Society: Development Tendencies, Arguments Pro and Con - Hovhannisyan, Hovhannes (Bulletin of Yerevan University E: Philosophy, Psychology, 2017)
The article presents the main stages of development and major modifications of the idea of civil society from Greek and Roman antique philosophy to modern researchers. It discusses two – broad (philosophical) and narrow (the third sector of organizing civil society) – perceptions of civil society and proposes corresponding definitions. Etatistic (controlled), liberal, conflicting, partnership, segmentational and linked models of civil society are analyzed. The expediency of linked and partnership models is substantiated from the position of security and harmonious development of the civic society.